Speckle contrast of interfering fluorescence X‐rays. (18th November 2022) - Trost, Fabian; Ayyer, Kartik; Oberthuer, Dominik; Yefanov, Oleksandr; Bajt, Saša; Caleman, Carl; Weimer, Agnes; Feld, Artur; Weller, Horst; Boutet, Sébastien; Koglin, Jason; Timneanu, Nicusor; et al.
Abstract : Methods are developed to quantify the degree of coherence of fluorescently emitted X‐rays from short‐pulse XFEL excitations. Applications to 3 fs and 15 fs excitations are shown. Abstract : With the development of X‐ray free‐electron lasers (XFELs), producing pulses of femtosecond durations comparable with the coherence times of X‐ray fluorescence, it has become possible to observe intensity–intensity correlations due to the interference of emission from independent atoms. This has been used to compare durations of X‐ray pulses and to measure the size of a focusedX‐ray beam, for example. Here it is shown that it is also possible to observe the interference of fluorescence photons through the measurement of the speckle contrast of angle‐resolved fluorescence patterns. Speckle contrast is often used as a measure of the degree of coherence of the incident beam or the fluctuations of the illuminated sample as determined from X‐ray diffraction patterns formed by elastic scattering, rather than from fluorescence patterns as addressed here. Commonly used approaches to estimate speckle contrast were found to suffer when applied to XFEL‐generated fluorescence patterns due to low photon counts and a significant variation of the excitation pulse energy from shot to shot. A new method to reliably estimate speckle contrast under such conditions, using a weighting scheme, is introduced. The method is demonstrated by comparing the speckle contrast of fluorescence observed with pulses of 3 fs to 15 fs duration.